Richard Guy Condon (1952-1995) - Wenzel, George W.; McCartney, Allen P. (ARCTIC, 1996)
On 7 September 1995, Rick Condon disappeared and is presumed to have drowned while conducting fieldwork in Chukotka. He, three colleagues, and five Siberian Yup'ik Eskimos from Sireniki were lost while traveling by small skin boat along the Bering Strait coast, between Sireniki and Provideniya in the Russian Far East. . True to arctic tradition, he had broad interests in northern peoples. His principal focus was Inuit adolescent development under conditions of modernity, but he also contributed to our knowledge of Inuit economy and ethnohistory, the impact of television and the media on Canadian Inuit, and historic arctic photography. His research on Inuit adolescence resulted in over two dozen articles and two books, . A third book, . had just gone to press at the time of his death. . We will remember Rick as a dedicated scholar-teacher and an excellent campmate, as adept with his banjo as he was with his laptop computer. Professional in every way, he was a major resource to colleagues and Inuit alike, a research referee who always encouraged new ideas and younger scholars, and a promoter of multidisciplinary northern sciences. At the time of his death, he was writing the first "real" northern mystery novel, a task to which he enjoyed devoting time while visiting Holman. Besides being an exceptional scholar, Rick was a humanist who was an active supporter of Amnesty International and a parent who saw to it that all his family enjoyed northern community ties. Rick worked closely with Pam [his wife] in Holman on several projects of their mutual interest, and he also took both his daughters to Holman on several occasions, where they were easily adopted into the community. . Rick was himself a scholar in "the best part of life," who built his life and career on compassion, hard work, insight, and dedication. .